Outburst mechanism and hazard prevention technique of limestone aquifer under isolated island panels - Wang, Wei; Wu, Yanjun; Shi, Yongli; Zhu, Jingzhong (Frontiers in Earth Science, 2025)
With the high-intensity mining activities and the selection of interval mining methods, a large amount of high-rank coal resources are left in the underground space (isolated islands). However, due to the complicated mining geological conditions, the coal resources in the isolated islands have not been fully extracted. In this paper, the mechanism of water inrush from limestone aquifers under isolated island panels is discussed from theoretical mechanics analysis, numerical simulation, discriminant criterion, the variation law of surrounding rock stress and water pressure, and floor failure depth. Meanwhile, we take the coal mining of the isolated island shaft in the Zhuzhuang colliery, Huaibei mining area, as an application case and propose the key technique of limestone water disaster prevention and control. Eventually, the treatment effect is validated by the practical work. The study results indicate that (1) the depth of the floor failure zone is 27.51 m and that the risk owing to water inrush of the panel floor in the isolated islands exists. The isolated coal pillar is more affected by the formation stress in numerical simulation, and the distribution of small stress on both sides of the panel floor and large stress in the middle area formed compared to non-isolated islands. The maximum stress of the panel floor is greater than that of mining without isolated islands. (2) The special drilling structures, stepwise gradient pressurization, and segmented sequential downward grouting technique are proposed to ensure the grouting effect under goaf. (3) Finally, the limestone water disaster regional treatment and control for the isolated island shaft is carried out and validated. The water level of ground boreholes and the water yield of underground directional boreholes verified the treatment effect. The theoretical results and engineering application in this study have significant implications for coal mining on other isolated islands affected by panel floor water damage.